Quality of Life and Cost Study of Rheumatoid Arthritis Therapy With Biological Medicines - Boyadzieva, Vladimira V.; Stoilov, Nikolay; Stoilov, Rumen M.; Tachkov, Konstantin; Kamusheva, Maria; Mitov, Konstantin; Petrova, Guenka I. (Frontiers in Pharmacology, 2018)
Biological medicines are considered as a cornerstone in the therapy of rheumatoid arthritis (RA). They change the course of the disease and improve the quality of life of patients. To this date there has been is no study comparing the quality of life of and cost of RA therapy in Bulgaria, this fact is what provoked our interest towards this research. The aim of this study is to analyse the cost and quality of life of patients with RA threated with biological medicines in Bulgaria. This is an observational, real life study of 124 patients treated with biological medicines during 2012-2016 at the University hospital “St. Ivan Riskli” in Sofia, specialized in rheumatology disease therapy. Patients were recruited after their consecutive transfer from non-biological to biological medicines. The yearly pharmacotherapy cost was calculated with tocilizumab (n=30), cetrolizmab (n=16), golimumab (n=22), etanercept (n=20), adalimumab (n=20), rituximab (n=16). Three measurements of the quality of life (QoL) were performed with EQ5D - at the beginning of the therapy, after 6 months and after 1 year of therapy. Cost – effectiveness was calculated for unit of improvement in EQ5D score for a one year period and decision model was built with TreeAgePro software. The observed cost of therapy varied between 12 thousand Euros for tocilizumab to 6 thousand Euros for rituximab. All biological medicines let to substantial increase in the quality of life of the patients. Patients on tocilizumab increased their QoL from 0.43 to 0.63 after 1 year ; on cetrolizumab from 0.32 to 0.56; on golimumab from 0.41 to 0.67; on etanercept from 0.45 to 0.62; on adalimumab from 0.43 to 0.57; on rhituximab from 0.46 to 0.66. The cost-effectiveness estimates of different biological therapies also varied between 66 to 30 thousand Euros for unit of improvement in the EQ5D during one the course of the year. Therapy with biological medicines improves statistically significant the quality of life of patients, measured through VAS and EQ5D scales. Despite the improvement in the quality of life all biological medicines appears not to be note cost-effective due to their high incremental cost-effectiveness ration (CER). Rituximab’s